The “Unlinkables”: A Case Series of Overcoming Social Determinants of Health for Successful Linkage to Care for HIV from the ED - Phillip Moschella; Mirinda Ann Gormley; Kiran Faryar (Clinical Practice and Cases in Emergency Medicine)
Introduction: Despite the success of emergency department (ED)-based universal HIV screening programs in select cities, widespread integration of similar programs across the United States has not followed. Within the US Centers for Disease Control and Prevention (CDC)-designated “Ending the HIV Epidemic (EHE)” areas, ED-based HIV screening is low. This case series highlights successful strategies for notification and linkage to care of patients with various challenging social determinates of health (SDoH). The goal is to inspire more EDs to offer universal HIV screening by providing insight into these challenging SDoH and successful strategies to overcome them. Case Series: We describe four cases, two from a site in upstate South Carolina and two from Cuyahoga County in Ohio, that highlight successful notification and linkage to care of these perceived “worst-case” scenarios. Both ED-based programs are located in CDC-designated EHE areas. We discuss ED screening opportunities and successful linkage for these minority patients (21–36 years of age), and highlight the concomitant and challenging mental health and substance use disorders, and SDoH that were overcome. All four of these patients are currently receiving treatment for HIV and 3 of the 4 have reached viral suppression. Conclusion: Despite challenging SDoH including unstable housing and lack of transportation, phone, and even legal identification documentation, these ED-identified patients with HIV were successfully notified of their disease status and linked to care. The patient navigators used perseverance, connections to local community resources, and leveraged family support to achieve linkage success. The cases serve as both a roadmap and source of inspiration to other EDs in priority EHE areas to begin ED HIV screening programs.